EXPERIMENTAL STUDY OF HOT WATER STORAGE TANKS FROM A DOMESTIC REFRIGERATOR - Marchi Neto, I.; Oliveira, S. D. R.; Padilha, A.; Scalon, V. L. (Revista de Engenharia Térmica, 2008)
The extreme necessity to diversify the sources of renewable energy motivates the search for methods of recycling of thermal energy losses of equipments. Thus, these energy losses can be used as a new source of energy for water heating and storage in a Domestic Hot Water Storage Tank (DHWST). Therefore, an experimental apparatus is proposed with a cylindrical tank for liquid storage. The main objective of this experimental test is the estimation of the coefficient of comprehensive energy performance (COP) relative to the system and the analysis of the hot water storage through the stratification technique. The storage and use of this form of energy utilizes a shell and tube heat exchanger, whose function is to condensate the cooling liquid using water in countercurrent, which substitutes the refrigerator finned condenser. Thermal energy losses are collected by the thermosiphon principle, and stored as sensible heat in the tank. The results showed the full operation of the modified refrigeration system as well as the storage of hot water at satisfactory thermal levels for domestic use, since this is a commercially manufactured refrigerator.